NGHIÊN CỨU ĐIỀU CHẾ VẬT LIỆU ĐIALĐEHYT XENLULO BẰNG PHƯƠNG PHÁP OXY HÓA PERIODAT VÀ CÁC TÍNH CHẤT CƠ LÍ CỦA NÓ - Hiền, Đào Trọng; Bưu, Ngô Quốc; Hà, Huỳnh Thị; Châu, Nguyễn Hoài (Vietnam Journal of Science and Technology, 2012)
PREPARATION OF DIALDEHYDE CELLULOSE BY USING PERIODATE OXIDATION METHOD AND ITS MECHANICO – PHYSICAL PROPERTIES Cellulosic fabric after being modified into dialdehyte cellulose is able to covalently bind bioactive enzyme which can be used for wound treatment. This report presents some results of our studies on the modification process of medical fabric materials made of from natural vietnamese cotton and physical-mechanical properties of the modified product. Fabric cellulose was modified into dialdehyde cellulose by using periodate oxidation method. In these studies, the oxidation levels of the cellulose are in a range of 1.7- 25%. At 0.05 M periodic acid, oxidation level of the cellulose reached plateau maximum value at a module of 20 after 18 hours of reaction. Several physical properties of the materials have been measured and assessed for appropriateness for usage in manufacturing wound dressings.